تلقي المنهج البنيوي التكويني عند الناقد الجزائري عمرو عيلان The Acquisition Of The Structural And Formative Approach" For The Algerian Critic " Amro Ailan - فهيمة, حمداوي (جامعة الوادي - University of Eloued, 2022)
وقفنا من خلال دراستنا هذه المعنونة بتلقي المنهج البنيوي التكويني عند الناقد الجزائري " عمرو عيلان" على أهم الأطر النظرية الفلسفية والنقدية الخاصة بالمنهج البنيوي التكويني من حيث مرجعياته الفلسفية،وأهم المفاهيم والمصطلحات والنقاد الخاصة بهذا المنهج، وفي الجانب التطبيقي هي دراسة في مجال نقد النقد معتمدين في ذلك على خطاب التحقيق من خلال دراسة الناقد الجزائري "عمرو عيلان" لروايات عبد الحميد بن هدوقة، مبرزين في ذلك خصوصيات المنهج البنيوي التكويني مفاهيميا واصطلاحيا، وكذا اعتماد الناقد "عمرو عيلان" على توظيف سوسيولوجيا النص الروائي وعلم السرد والسيميائية. Abstract Through the study which is entitled by " The acquisition of the Structural and formative approach" for the Algerian critic " Amro Ailan", we got across the most important the ioritical, philosophical and critical frames of the mentioned approach from its philosophical reference besides the most noticable concepts, vocabulary and critics of it. In the practical field, it was a study in the criticism of criticism domain, applying " the investigation speech" by using the critic Amro' Ailan s study of Abd Elhamid Ben Sadoka' s novels; trying to highlight the specifics of the Structural formative approach besides relying on the use of the textual novelistic sociology, the narrative science and semiotics.
مقال
Keywords: البنية،البنية الدالة،الوعي الممكن،الوعي الكائن،سوسيولوجيا النص الروائي.